STUDENTS’ PERCEPTION OF CLASSROOM ENVIRONMENT OF WRITING CLASS - Indah Rahmalia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
The purpose of this study was to find out students’ perception toward classroom environment in writing class at STKIP AbdiPendidikanPayakumbuh. This study was carried out of descriptive research that undertaken through phenomenological approach by employing questionnaire to 24 students selected by using purposive sampling technique. The findings of this study show that the students have good perception toward classroom environment of writing class by mean score is 79.25. From the interval statistical, the mean score belongs to good classification. It can be concluded that the students perceived their classroom as having positively atmosphere which extrinsically motivated them in learning, especially in writing.